The Imperative for Patient-Centered Clinical Decision Support. Issue 1 (30th May 2018) - Marcial, Laura Haak; Richardson, Joshua E.; Lasater, Beth; Middleton, Blackford; Osheroff, Jerome A.; Kawamoto, Kensaku; Ancker, Jessica S.; van Leeuwen, Danny; Lomotan, Edwin A.; Al-Showk, Shafa; Blumenfeld, Barry H.
This commentary introduces the Patient-Centered Clinical Decision Support (PCCDS) Learning Network, which is collaborating with AcademyHealth to publish "Better Decisions Together" as part of eGEMs . Patient-centered clinical decision support (CDS) is an important vehicle to address broad issues in the U.S. health care system regarding quality and safety while also achieving better outcomes and better patient and provider satisfaction. Defined as CDS that supports individual patients and their care givers and/or care teams in health-related decisions and actions, PCCDS is an important step forward in advancing endeavors to move patient-centered care forward. The PCCDS Learning Network has developed a framework, referred to as the Analytic Framework for Action (AFA), to organize thinking and activities around PCCDS. A wide array of activities the PCCDS Learning Network is engaging in to inform and connect stakeholders is discussed.